Investigation of 4-Nitro-N, N-diphenylaniline as a chemical tracer under high pressure high temperature reservoir conditions for enhanced oil recovery applications - Subhadip Maiti; Nishant Kumar Choudhary; Kiran R. Gore; Sandeep D. Kulkarni (Journal of Petroleum Exploration and Production Technology)
Abstract The identification of multiple distinguishable chemical tracers is crucial for determining well-to-well connectivity and optimising oil recovery processes, especially in an oilfield with a complex well matrix. In this regard, the present study investigates a novel chemical tracer 4-Nitro-N, N-Diphenylaniline (N-TPA) and compares its performance against an industry-standard water-soluble tracer, 4-Fluorobenzoic Acid (4-FBA). The purity of the synthesised N-TPA was first confirmed to be greater than 98% based on nuclear magnetic resonance (NMR) analysis. Ultraviolet (UV) and high-performance liquid chromatography (HPLC) techniques were established to measure the ppm-level concentrations of 4-FBA and N-TPA in the standard brine solutions. On the HPLC analysis, the N-TPA specifically exhibited a distinct retention time of approximately ≈ 15.9 min, whereas the FBA tracers featured retention times ranging from approximately ≈ 1.9 to 9 min. As a result of these distinct retention times, the novel tracer could easily be used along with conventional tracers without encountering any overlap issues during their identification in the producer wellbores. The dynamic degradation response of N-TPA for a temperate range of (120–180 °C) was also investigated experimentally and compared with the industry-standard tracer; the empirical modelling of the time-temperature dynamics revealed that the decay response of both tracers was comparable. The novel tracer was also investigated experimentally for rock adsorption by exposing it to the sandstone rock particles (150–250 μm) at 121 °C; it was demonstrated that the tracer showed minimal adsorption at the rock surface (< 1%), which was equivalent to the industry-standard tracer. A core flooding experiment was conducted using the novel tracer solution on a rock sample from the Rajasthan, India, oilfield. The resulting tracer breakthrough curves provided quantitative data on swept pore volume, Lorentz coefficient (0 ≤ Lc ≤ 1), and sweep efficiency. The findings indicate that the temperature stability of N-TPA and distinct HPLC retention time make it a viable candidate as a novel tracer. The novel tracer could be used in combination with or standalone along with the industry-standard tracers to optimise oil recovery from a wellbore pattern further. Graphical abstract